2023
DOI: 10.1007/s00381-023-05952-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of pediatric pineal region tumors at a single institution

Abstract: Purpose: To identify factors of a worse prognosis among different histological types of pineal region tumors in pediatric patients treat at a single institution in a 30-year period.Material and Methods: 151 pediatric patients (< 18 years of age) treated between 1991 and 2020 were analyzed. Kaplan-Meyer survival curves were created and the log-rank test was used to compare the main prognostic factors in the different histological types.Results: Germinoma was found in 33.1%, with an overall 60-month survival rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Cavalheiro et al reported that the overall survival rate for patients with germinomas at 1, 2, and 5 years was 93.7, 93.7, and 88%, respectively, whereas Valsechi et al determined that the 5-year survival rate for germinomas was 88%. 5,6 Previous studies have identified prognostic factors for pineal tumors, including gender, age, and the extent of resection. In the present study, the HALP score is strongly associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavalheiro et al reported that the overall survival rate for patients with germinomas at 1, 2, and 5 years was 93.7, 93.7, and 88%, respectively, whereas Valsechi et al determined that the 5-year survival rate for germinomas was 88%. 5,6 Previous studies have identified prognostic factors for pineal tumors, including gender, age, and the extent of resection. In the present study, the HALP score is strongly associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to Valsechi et al, the predictor of a poor prognosis in germinoma was female gender, whereas male was associated with an unfavorable prognosis in pineoblastoma. 5 Additionally, Cavalheiro et al found that entire resection was a potential predictor of outcome in pediatric patients with pineal area tumors. 6 In a population-based study, older age, male gender, nongerm cell tumor, and receiving chemotherapy were significantly associated with prognosis.…”
Section: Introductionmentioning
confidence: 99%